Arthropod diversity during vegetative growth phase of rice field at Kedah, Malaysia - Sahari, Farah Husna; Abd Manaf, Latifah (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
Other than being wetland ecosystems that occupy the largest area of the agricultural land in Malaysia, rice field is also a home to numerous organisms. This study attempts to investigate the arthropod diversity during the vegetative growth phase of rice field at Kedah. Six sampling points has been chosen spreading across Kedah districts which are, Kubang Pasu, Kota Star, Padang Terap, Pendang, Sik, and Bandar Baharu. Sweeping net, yellow pan and light traps are the methods used for insect trapping. Arthropod diversity was calculated using Shanon-Wiener Diversity Index. The outcome of the study shows that, Kubang Pasu has the highest diversity index value with 3.218 and Pendang has the lowest diversity index value. A total of 2434 insect specimen had been collected consisting of 9 orders and 66 species. Among the 66 species collected, 23 species has been identified as a rice pest.